Particles trajectories finding in the vertex detector of the CBM experiment - I. S. Kulakov; I. V. Kisel; M. V. Zyzak (Ядерна фізика та енергетика)
Particles trajectories search in the vertex detector is a basis of collision reconstruction of the CBM experiment (GSI, Germany). The requirements for a modern experiment with fixed target are very high, specifically: up to 107 collisions per second, up to 1000 charged particles in the detector, inhomogeneous magnetic field, about 85 % additional fake combinatorial measurements in the detector, full on-line event reconstruction. Cellular automaton method is used to reconstruct charged particles trajectories. Description of the algorithm and results of tests are presented.